POTENSI TEKNOLOGI INSEMINASI BUATAN PADA PENINGKATAN PRODUKTIVITAS ITIK TURI LAMONGAN - Restiadi, Tjuk Imam; Hernawati, Tatik; Rahardjo, Dadik; Widiyatno, Thomas V. (Ovozoa: Journal of Animal Reproduction, 2019)
Duck is one of the most poultry that potential can be best developed for its productivity to be used for meat and eggs. The obstacles faced by farmers include productivity of low and not meat and duck eggs. Application of science and technology through the development of reproductive technology of Artificial Insemination (AI) by conducting cross-breeding. The application to cross ducks is very beneficial because in addition to being economical it is also efficient. AI duck is very easy to apply and fast, does not require a complicated and long process as in large livestock. Ducks from artificial insemination are produced in Turi local female ducks (Anas plathirinchos) with plump males (Cairina moschata). The reason for the crossing is because the duck man has a body size that is too large compared to the local duck, so it can produce offspring with rapid growth and large body size. The conclusion is that duck farming with IB in Tawangrejo Turi Lamongan is useful for increasing body weight and productivity.